Microstructure and wear characterization of Al2O3 reinforced silver coated copper matrix composites by electroless plating and hot pressing methods. (June 2021) - Güler, Onur; Varol, Temel; Alver, Ümit; Kaya, Gürkan; Yıldız, Fatih
Graphical abstract: Highlights: Obtaining homogeneous electroless silver coating layer on copper powders. Production of the novel silver coated copper matrix composites. Production of the composites with homogeneous alumina particle dispersion. Obtaining composites with improved electrical conductivity and hardness. Obtaining silver coated copper matrix composites with improved wear resistance. Abstract: Copper-based composites are frequently used in areas such as contacts, contactors, switches etc. where electrical conductivity and tribological properties play a critical. In this work, the microstructure, electrical and wear properties of silver plated copper powder matrix and Al2 O3 reinforced composites fabricated by electroless silver plating (ESP) and hot pressing were investigated. Copper powders with different morphologies fabricated by mechanical milling (MM) were used as matrix while different Al2 O3 contents (0.5 %, 1 %, 2 %, 3 % and 5 wt. %) were used as reinforcement materials for the production of composites. The results showed that the ESP layer on milled copper powders for 2 h was quite uniform and the Al2 O3 distribution was better in these composites than others. The highest hardness value (∼125 HB) and the lowest wear rate (1.5E-04 mm 3 /Nm) were observed in composites including silver plated copper matrix powders and Al2 O3 (3 wt. %). Although the electrical conductivity values decrease with increasing Al2 O3 ratio for all composites, the decrease in electrical conductivity was only up to about 86 %IACS in composites where the highest hardness value was obtained. Besides, the dominant wear mechanism was abrasive wear with grooves and scratches while the lowest wear scar width (about 557 μm) was observed in these composites.